MIF promoter polymorphisms are associated with epiretinal membrane but not retinal detachment with PVR in an american population. (August 2019) - Cebulla, Colleen M.; Stevenson, William; Van Law, Heather; Heisler-Taylor, Tyler; Hamadmad, Sumaya; Shah, Mohd Hussain; Kim, Bongsu; Davidorf, Frederick H.; Ohr, Matthew; Wells, Michael; Yanoga, Fatoumata; Chang, Susie; et al.
Highlights: MIF promoter polymorphisms rs5844572 and rs755622 are implicated in many inflammatory conditions. Case-cohort genetic association study in the US from 2012 to 2018. 601 study subjects: RD (n = 180), RD with PVR (n = 120), ERM (n = 100) and 201 controls. Significant association of rs755622 (C/C) and homozygous C7 haplotype with ERM. No association was found between RD or PVR and the MIF polymorphisms.